ISOLATION OF ARBUTIN FROM SUKUN (ARTOCARPUS ALTILIS [PARK.] FOSBERG.) LEAF AND STEM EXTRACTS AS A TYROSINASE INHIBITOR - Zuraida Sagala; Risty Setyati Ashari (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2025)
This study aims to isolate arbutin compounds from 70% ethanol extract of breadfruit (Artocarpus altilis) leaves and stems, determine the levels of arbutin in the extract, and evaluate the inhibitory activity of tyrosinase enzyme. Isolation was carried out through extraction and fractionation methods using n-hexane, ethyl acetate, and butanol solvents. Identification of arbutin was carried out by High Performance Liquid Chromatography (HPLC) based on the suitability of retention time to the standard. The results showed that the level of arbutin in 70% ethanol extract of breadfruit leaves was 14.84 mg/L and breadfruit stems was 14.81 mg/L. Tyrosinase activity test showed that ethyl acetate fraction of breadfruit leaves had the highest effectiveness as tyrosinase inhibitor with IC₅₀ value of 355.24 ppm, compared to crude extract and other fractions. Although the activity has not matched the positive control kojic acid (IC₅₀ = 39.28 ppm), these results indicate the potential of breadfruit leaf and stem extracts as a source of natural active ingredients for skin lightening